2007
DOI: 10.1590/s1413-86702007000200011
|View full text |Cite
|
Sign up to set email alerts
|

Short-interfering RNAs as antivirals against rabies

Abstract: This study aimed to test in vitro a RNA-interference based antiviral approach for rabies with short-interfering RNAs (siRNAs) against rabies virus nucleoprotein mRNA. BHK-21 cells were infected with serial dilutions of PV rabies virus strain and transfected with a pool of three siRNAs. Direct immunofluorescence staining showed a 5-time decrease in virus titer when compared to a non-treated plate, showing a promising new approach to the development of antivirals for rabies treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…These results demonstrate that all three siRNAs used in this study are similarly efficient when used in separate or as pools, as described by Brandão et al (2007).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These results demonstrate that all three siRNAs used in this study are similarly efficient when used in separate or as pools, as described by Brandão et al (2007).…”
Section: Discussionsupporting
confidence: 78%
“…The siRNAs described by Brandão et al (2007) (Table 1), complementary to different regions of RABV N protein mRNA, were synthesized in a duplex format with two deo-xi-timidines at the 3′ end of each sense and anti-sense strands and resuspended as instructed by the manufacturers (Invitrogen, Carlsbad, CA, USA) and used for cell and mice trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a dramatic increase in the number of new and developing viral therapeutic options including RNA-based therapies such as RNA interference (RNAi), aptamers and microRNA (miRNA)-based therapies. RNAi has thus far only been applied in a limited number of studies with regards to rabies [174,175,176,177,178,179,180], but has shown great potential, both within rabies, as well as in other viral diseases where research is at a more advanced stage [181]. However, several challenges still remain, including that of identifying the ideal targets for knockdown and the means of targeted delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, plasmids encoding siRNA, or another form of RNAi that target specific RABV genes, were constructed and tested for anti-rabies efficacy [124,125,126]. Although the plasmid-based approaches achieved some degree of anti-rabies effect, the low efficiency of siRNA delivery hindered the substantial protection against RV through anti-rabies RNAi approach.…”
Section: Other Novel Modalities For Rabies Control and Preventionmentioning
confidence: 99%